Hepatic artery occlusion in liver transplantation: What counts more, the type of reconstruction or the severity of the recipient's disease?. Issue 6 (6th June 2018) - Oberkofler, Christian E.; Reese, Tim; Raptis, Dimitri A.; Kuemmerli, Christoph; de Rougemont, Olivier; De Oliveira, Michelle L.; Schlegel, Andrea; Dutkowski, Philipp; Clavien, Pierre‐Alain; Petrowsky, Henrik
Abstract : Although the type of hepatic artery revascularization technique is known to have an impact on patency rates, independent perioperative risk factors on patient outcomes are poorly defined. All consecutive adult patients undergoing cadaveric liver transplantation (n = 361) from July 2007 to June 2016 in a single institution were analyzed. Primary outcomes were early (<30 days) hepatic artery occlusion and primary hepatic artery patency rate. A multivariate model was used to identify independent risk factors for occlusion and the need of arterial conduit, as well as their impact on graft and patient survival. Arterial revascularization without additional reconstruction (end‐to‐end arterial anastomosis [AA]) was performed in 77% (n = 279), arterial reconstruction (AR) in 15% (n = 53), and aortohepatic conduit (AHC) in 8% (n = 29) of patients. AHC had the highest mean intraoperative flow (275 mL/minute; P = 0.02) compared with AA (250 mL/minute) and AR (200 mL/minute; P = 0.02). There were 43 recipients (12%) who had an occlusive event with successful revascularization in 20 (47%) recipients. One‐year primary patency rates of AA, AR, and AHC were 97%, 88%, and 74%, respectively. Aortic calcification had an impact on early occlusion. AR (odds ratio [OR], 3.68; 95% confidence interval [CI], 1.26‐10.75; P = 0.02) and AHC (OR, 6.21; 95% CI, 2.02‐18.87; P = 0.001) were independent risk factors for early occlusion. Dyslipidemia additionally independently contributed to early occlusion (OR, 2.74; 95% CI, 0.96‐7.87; P = 0.06). The 1‐ and 5‐year graft survival rates were 83% and 70% for AA, 75% and 69% for AR, and 59% and 50% for AHC ( P = 0.004), respectively. In conclusion, arterial patency is primarily determined by the type of vascular reconstruction rather than patient or disease characteristics. The preoperative lipid status is an independent risk factor for early occlusion, whereas overall occlusion is only based on the performed vascular reconstruction, which is also associated with reduced graft and patient survival. Liver Transplantation 24 790–802 2018 AASLD.